Aryl Hydrocarbon Receptor (AhR) Modulates Cockroach Allergen-Induced Immune Responses through Active TGFβ1 Release - Yufeng Zhou; Sarah Mirza; Ting Xu; Priya Tripathi; Beverly Plunkett; Allen Myers; Peisong Gao (Hindawi Limited, 2014)
Background. Aryl hydrocarbon receptor (AhR), a multifunctional regulator that senses and responds to environmental stimuli, plays a role in normal cell development and immune regulation. Recent evidence supports a significant link between environmental exposure and AhR in the development of allergic diseases. We sought to investigate whether AhR plays a role in mediating cockroach allergen-induced allergic immune responses. Methods. AhR expression in human lung fibroblasts from asthmatic and healthy individuals and in cockroach extract (CRE) treated human lung fibroblasts (WI-38) was examined. The role of AhR in modulating CRE induced TGFβ1 production was investigated by using AhR agonist, TCDD, antagonist CH122319, and knockdown of AhR. The role of latent TGFβ1 binding protein-1 (LTBP1) in mediating TCDD induced active TGFβ1 release was also examined. Results. AhR expression was higher in airway fibroblasts from asthmatic subjects as compared to healthy controls. AhR in fibroblasts was activated by TCDD with an increased expression of cyp1a1 and cyp1b1. Increased AhR expression was observed in CRE-treated fibroblasts. Importantly, CRE induced TGFβ1 production in fibroblasts was significantly enhanced by TCDD but inhibited by CH122319. Reduced TGFβ1 production was further confirmed in fibroblasts with AhR knockdown. Moreover, AhR knockdown inhibited CRE induced fibroblast differentiation. Furthermore, TCDD induced active TGFβ1 release was significantly inhibited by LTBP1 knockdown. Conclusion. These results provide evidence for the role of AhR in modulating cockroach allergen-induced immune responses through controlling the active TGFβ1 release, suggesting a possible synergistic effect between exposure to allergens and environmental chemicals on the development of allergic diseases.